Long-range persistence in sea surface temperature off the coast of central California. (January 2019) - Breaker, Laurence C
We estimate long-range persistence in ocean surface temperature off the coast of central California, a region where similar observations have not been made. The database consists of 20-year records of daily sea surface temperature from three locations: Pacific Grove and Granite Canyon along the coast, and Southeast Farallon Island located 40 km off the coast and slightly further north. Long-range persistence is important for a number of reasons: on the negative side, it can have serious detrimental effects for statistical inference and on the positive side, it provides access to the ocean's memory which can lead to a greater understanding of the processes involved and thus to better prediction. Long-range persistence also provides important insights into the relationship between the scaling that is obtained and the time scales employed. The first step in the analysis was to remove the annual cycle from the data at each location because of its detrimental effect on estimating long-range persistence. Then detrended fluctuation analysis was used to calculate long-range persistence where a single scaling exponent is obtained that relates the magnitudes of the fluctuations in the data to the time scales involved. Similar scaling exponents were obtained for Granite Canyon and Pacific Grove with values of 1.04 and 1.05, respectively. At Southeast Farallon Island, a value of 1.16 was obtained. The increase in the scaling exponent at Southeast Farallon Island is consistent with observations made elsewhere and model results, which indicate that as coastal influence decreases further offshore, the scaling exponents for sea surface temperature tend to increase. Because Southeast Farallon Island is exposed to subarctic waters offshore, whereas Pacific Grove and Granite Canyon are exposed to warmer waters from the California Undercurrent along the coast, these exposures to different water masses may contribute to the observed change in scaling behavior.